Poisoning the Mind : Arsenic Contamination and Cognitive Achievement of Children - Asadullah, Mohammad Niaz (World Bank, Washington, DC, 2012)
Bangladesh has experienced the largest mass poisoning of a population in history owing to contamination of groundwater with naturally occurring inorganic arsenic. Continuous drinking of such metal-contaminated water is highly cancerous; prolonged drinking of such water risks developing diseases in a span of just 5-10 years. Arsenicosis-intake of arsenic-contaminated drinking water-has implications for children's cognitive and psychological development. This study examines the effect of arsenicosis at school and at home on cognitive achievement of children in rural Bangladesh using recent nationally representative school survey data on students. Information on arsenic poisoning of the primary source of drinking water-tube wells-is used to ascertain arsenic exposure. The findings show an unambiguously negative and statistically significant correlation between mathematics score and arsenicosis at home, net of exposure at school. Split-sample analysis reveals that the effect is only specific to boys; for girls, the effect is negative but insignificant. Similar correlations are found for cognitive and non-cognitive outcomes such as subjective well-being, that is, a self-reported measure of life satisfaction (also a direct proxy for health status) of students and their performance in primary-standard mathematics. These correlations remain robust to controlling for school-level exposure.